Evaluation of new antibodies for the detection of rabies virus in formalin fixed brain tissue samples - Jáuregui, Gloria R.; Fontana, Diego; Micheloud, Juan F.; Prieto, Claudio; Delgado, Fernando (Brazilian Journal of Veterinary Pathology, 2019)
Rabies is an important zoonosis with impact on livestock production. The diagnosis is usually based on the rabies virus detection in fresh or refrigerated brain samples by direct immunofluorescence (IF) performed on fixed brain smears. The aim of this study was to evaluate the performance of 6 monoclonal and 1 rabbit-polyclonal new antibodies for rabies diagnostic by using immunohistochemistry (IHC), which detects the agent on formalin fixed paraffin embedded tissues samples. Tested with 2 positive and 2 negative cows for rabies at dilutions 1/200 and 1/1000, obtained immunostaining was strong for one monoclonal and weak for the polyclonal at both dilutions. For 3 monoclonals, the immunostaining was weaker at 1/1000 and was negative at both dilutions for 2 monoclonals. Unwanted background was absent and negative samples remained clear for all antibodies. When the first monoclonal was applied on sections of brain of 19 cows with Rabies and 41 control cows at 1/1000 dilution, immunohistochemistry recognized all positive samples and was negative for all control cows. The number of cases analyzed did not allow estimating sensitivity and specificity of the tested assay, but the correlation observed between IF and IHC in both positive and negative samples suggested that accuracy of the test might be good. The results indicated that the tested antibody can detect the rabies virus on formalin fixed tissue samples, and that immunohistochemistry can complement other confirmatory tests when those cannot be performed.